Pengaruh Perbedaan Mesh Size pada Alat Tangkap Gillnet terhadap Hasil Tangkapan Ikan Senangin ( Eleutheronema Tetrandactylum) di Kecamatan Gadingrejo Kota Pasuruan - Rutbatun Sakinah; Sumaryam Sumaryam; Yusrudin Yusrudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Capture fisheries are one of the most contributing sectors in producing fishery products.The fourfinger threadfin (Eleutheronema tetradactylum) is one of the key commodities in the capture fisheries sector of Pasuruan City. The catch yield of this species is influenced by the mesh size of the gillnet used. This study aimed to determine the effect of different mesh sizes on the catch yield of fourfinger threadfin and to identify the most effective mesh size. The research was conducted using an experimental fishing method with a Randomized Block Design (RBD) comprising three gillnet mesh size treatments: 1.75 inches, 2.5 inches, and 4 inches, with nine fishing trips. Data on catch weight and number were analyzed using a One-Way ANOVA followed by the Least Significant Difference (LSD) test. The ANOVA results showed an F-value of 10.083 with a significance level of 0.001 (p-value < 0.05), indicating a significant difference in the catch weight of fourfinger threadfin (Eleutheronema tetradactylum) among the mesh size treatments. This finding suggests that mesh size has a significant effect on catch weight, with the 2.5-inch mesh size being the most effective for catching fourfinger threadfin in the Madura Strait, as it produced the optimal catch weight compared to 1.75-inch and 4-inch mesh sizes.